Síntesis por el método de combustión en solución y caracterización del BiFeO3 - Peñalva Sánchez Jhon Jhonathan (2018)
In this work, bismuth ferrite (BiFeÜ3) was prepared by solution combustión method. The single phase and good crystallization of BiFeÜ3 was obtained at a temperature of 500°C. The resulting sample was structurally characterized by X-ray diffraction (XRD), identifying the characteristic peaks of the phase BiFeÜ3. The Rietveld refinement of the X-ray diffraction pattern was performed, which indicates the existence of a distorted hexagonal perovskite structure (group space - R3c). The average crystallite size of the BiFeÜ3 was estimated from X-ray diffractogram and the Scherrer formula, obtaining a crystal size of 27 nm confirming the results of the literature. The morphological analysis was determined by scanning electron microscopy (SEM), this analysis shows us pores and grains at a scale of 1 pm in the BiFeÜ3 sample. The elemental analysis by X-ray dispersive energy spectroscopy (EDS) determined only the elements Bi, Fe and Ü in the percentage ratio close to the ideal for BiFeÜ3. The experimental band gap (Eg) was obtained from the analysis of UV-Vis diffuse reflectance spectra (DRS) through the Kubelka Munk function and from the Tauc equation, resulting in an Eg value of 2.20 eV. The magnetic response of the product BiFeÜ3 in the magnetic field was also analyzed and evaluated by vibrating sample magnetometry (VSM) revealing a weak ferromagnetism. The characteristic of the electronic structure of BiFeÜ3 through the Quantum Espresso software in which the density of the total and partial states of BiFeÜ3 were calculated, show us between the Ü2p states and Fe3d a band gap Eg of 1.97 eV.